Faktor Fundamental dan Risiko Sistematis Terhadap Return Saham: Studi Pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Rais, Anisatun Humayrah; Br. Ginting, Crish Dayanti; Yusuf, Yulia Yunita; Hidayatullah, Andi Muh. Syukur (PT Bone Jaya Kreatif, 2024)
This research aims to analyze the influence of company fundamental factors as measured by return on equity, price earnings ratio, debt to equity ratio, earnings per share, and dividend payout ratio on stock returns through systematic risk. The population and sample in this study were 22 companies and 110 observations of companies in LQ45 listed on the Indonesia Stock Exchange for the 2019-2023 period. Data analysis in this study used multiple liner regression and the Sobel test. The research results show that the company's fundamental factors as measured by return on equity, price earning ratio, debt to equity ratio, earnings per share, and dividend payout ratio influence stock returns. Furthermore, the results of the Sobel test show that systematic risk is able to mediate the relationship between company fundamental factors as measured by return on equity, price earnings ratio, debt to equity ratio, earnings per share, and dividend payout ratio on stock returns..